Socioeconomic disparities in risk perceptions and precautionary actions against COVID-19 among the working age population aged 18-59 in Japan: a cross-sectional study - Kyoko Shimamoto; Yoko Ibuka (BMJ Publishing Group, 2024)
Introduction Risk perceptions and precautionary actions against COVID-19 have been reported to be generally insufficient globally, and differences by subpopulation group have been concerning, as a key driver to widening health gaps. Although a body of literature examined these key constructs, critical comparative examinations of various risk perceptions and precautionary actions by socioeconomic group are still limited in Japan and Asia.Methods This study examines subjective and objective risk perceptions and precautionary actions against COVID-19 infection among the general working age population aged 18-59 in Japan, focusing on the differences by socioeconomic group and health status. A cross-sectional survey was conducted in March 2021, using an online self-reporting questionnaire, in selected prefectures in Japan where COVID-19 infection cases ranked the highest. Participants were randomly recruited, and quota sampling methods were employed with the weighting of the sample distribution by geographic location (n=2764).Results Subjective and objective risk perceptions and precautionary actions were significantly related to several of the socioeconomic variables, including gender, income, employment and household composition, as well as self-reported health status. These disparities were substantial even with the key basic preventive behaviour including mask wearing, avoidance of large gatherings and hand washing. Further, these risk perceptions and precautionary actions showed unexpected relationships with socioeconomic position and health status, contrary to existing evidence or theory, particularly among younger generations and worse health populations.Conclusions This evidence suggests that risk perceptions and precautionary actions do not always seem to align, and their disparities by socioeconomic group and health status have been underscored in Japan, which may suggest complex and distinct pathways by subpopulation group. Further evidence and strategies for COVID-19 and other infectious disease prevention would be critical in transitions of the infectious disease prevention and control strategy, targeting both the high-risk population group and higher risk-taking group.